Studies on photochromic and potentially mesogenic mercury(II) dithizonates - Cromhout, Natalie Lyn (Department of Chemistry, 2016)
The 4-( 4 '-n-alkoxybenzylideneanilino )mercury(II) dithizonates, CₙH₂ₙ₊₁ OC₆H₄CH=C₆H₄-Hg(HDz) (n = l, 4, 12, 14 or 18), were prepared by complexation of dithizone (1,5-diphenyl- thiocarbazone, H 2 Dz) with the corresponding 4-(4'-n-alkoxybenzylideneanilino)mercury(II) acetates. The 4-( 4 '-n-alkoxybiphenyl)mercury(II) dithizonates, CₙH₂ₙ₊₁ OC6H4 C6H4- Hg(HDz) (n = 4, 5, 10, 14 or 18), were similarly prepared by reaction of dithizone with the appropriate 4-(4'-n-alkoxybiphenyl)mercury(II) bromides, although the latter compounds, derived from the 4-n-alkoxy-4'-bromobiphenyls, were not isolated. The preparation of the 4- ( 4'-n-octyloxyazobenzene)mercury(II) dithizonate, C₈H₁₇OC₆H₄N=NC₆H₄Hg(HDz),from 4-n-octyloxy-4'-bromoazobenzene was attempted but the chosen synthetic method was not successful. The thermal behaviour of those series of compounds isolated was investigated by polarized optical microscopy and differential scanning calorimetry. The organomercury(II) acetates displayed a limited, poorly-defined mesomorphism and the type of any mesophase formed remains unidentified. The 4-n-alkoxy-4'-bromobiphenyls (alkoxy = CₙH 2 n+ 1 0, n = 3-5, 10-12, 14-16 or 18) exhibited liquid crystalline behaviour within a broad temperature range for the compounds with n ~ 10 and the nature of the mesophases was tentatatively assigned as smectic D and C. The 4-n-alkoxy-4'-bromoazobenzenes (alkoxy = CₙH 2 n+I0, n = 5, 10, 12 or 14) showed monotropic (n = 5, 10 or 12) or enantiotropic (n = 14) nematic and smectic A mesophases. However, none of the dithizonate derivatives was mesomorphic and this was attributed to the geometry of the dithizonate ligand. The organomercury(II) dithizonates were photochromic in organic solvents, displaying reversible colour changes from yellow to blue on irradiation with visible light. The visible absorption spectra of these solutions were recorded and appeared to be independent of the nature of the long-chain organic ligand. This photochromism was not observed in the solid state.